Synthesis of Rice Husk-Based Biocomposites Coated with Sodium Alginate and Their Use in Congo Red Dye Adsorption - Purwiandono, Gani; lestari, puji; Egi Saputra, Noventa (Chemistry Department, Universitas Islam Indonesia, 2024)
In this study, synthesis of a sodium alginate-coated rice husk-based biocomposite as a substitute adsorbent to lessen the negative impacts of congo red dye was conducted. A calcium chloride (CaCl2) solution was used in the sonication and encapsulation processes to produce the biocomposite material. X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Fourier Transform Infrared (FTIR) Spectroscopy were used to characterize the biocomposite material. Adsorption experiments showed that the optimum pH was 3 and the dye concentration was varied between 10 and 50 ppm and adsorbent mass between 0.05 and 1.5 grams. Adsorption kinetics followed the pseudo-second-order linear model, while the adsorption isotherm model matched the Freundlich model. According to these results, biocomposites of rice husk and sodium alginate have a potential to be an environmental-friendly way to manage the textile waste.